Climbing machine for pole-like object. - Wan Ismail, Wan Ishak; Shokripour, Hamed (2010)

(untitled)
A machine (100) capable of climbing pole-like object comprises a frame (110) with a central hollow (105) that the frame is telescopically adjustable to change size of the hollow (105) to enclose circumference of the pole-like object; at least one pair of opposite facing rotatable wheels (120,130) mounted on the frame and positioned within the enclosed hollow that each of the rotatable wheel is driven by a motor respectively; a tilt sensor (160) located in the machine which is capable of continuously measuring tilt angle of the frame (110) in relative to the horizontal planar; a microcontroller (170) in communication with the motors (122, 132) and able to control speed of each separated motor; wherein the wheels (120,130) resiliently clamp onto the surface of the object and rotate to move the machine upward or downward along the pole-like object and speed of the motor tilts at a higher angle is decreased by the microcontroller (170) in proportion to the measured tilt angle received from the tilt sensor (160).